Rozwiaz rownanie:
a) o,2x + 0,3 = 1,3
b)5x - 0,8 = 0,1 + 2x
c) 8x - 0,2 =8x - 0,1
d) 0,01x +17 = -0,16x
e)-0,07(10x - 1)= 0,3x
f) 0,83 + 0,82 = 0,23x + 1,52
g) 0,6x + 2(0,1x - 0,1) = 0,2(x + 1)
h) 0,7(x+2) = 0,4(x+1) + 0,3x +1
i) 0,15(2x+4) = 2(1,3 + 0,3x) - 0,6
j)0,1(x + 1) - 0,05(3x - 10)= 0,4 -0,35x



zad8
a) 4x - 3 =3x+5
b)5x+2=7-3x
c) 3(x-1)=0
d)-6(x+1)=24
e)-7(x-2)=3x-1
f)4(x-1)=6(1+x)

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-10T16:13:06+01:00
A) o,2x + 0,3 = 1,3
0,2x=1,3-0,3
0,2x=1 /:0,2
x=5
b)5x - 0,8 = 0,1 + 2x
5x-2x=0,1+0,8
3x=0,9 /:3
x=0,3
c) 8x - 0,2 =8x - 0,1
8x-8x= -0,1+0,2
0x=0,1
d) 0,01x +17 = -0,16x
0,01x+0,16x=-17
0,17x=-17 /:0,17
x=-0,01
e)-0,07(10x - 1)= 0,3x
-0,7x-0,07=0,3x
-0,7x-0,3x=0,07
-x=0,07
x=-0,07
f) 0,83 + 0,82 = 0,23x + 1,52
-0,23x=1,52-0,83-0,82
-0,23x=- 0,13 /: 0,23
x=
g) 0,6x + 2(0,1x - 0,1) = 0,2(x + 1)
0,6x+0,2x-0,2=0,2x+0,2
0,6x+0,2x-0,2x=0,2+0,2
0,6x=0,4 /:0,6
x=0,(6)
h) 0,7(x+2) = 0,4(x+1) + 0,3x +1
0,7x+1,4=0,4x+0,4+0,3x+1
0,7x-0,4x-0,3x=0,4+1-1,4
0x=0
i) 0,15(2x+4) = 2(1,3 + 0,3x) - 0,6
0,3x+0,6=2,6+0,6x-0,6
0,3x-0,6x=2,6-0,6-0,6
-0,3x=1,4 /: (-0,3)
x= -4,(6)
j)0,1(x + 1) - 0,05(3x - 10)= 0,4 -0,35x
0,1x+0,1-0,15x-0,5=0,4-0,35x
0,1x-0,15x+0,35x=0,4-0,1+0,5
0,3x=0,8 /:0,3
x=2,(6)



a) 4x - 3 =3x+5
4x-3x=5+3
x=8
b)5x+2=7-3x
5x+3x=7-2
8x=5 /:8
x=0,625
c) 3(x-1)=0
3x-3=0
3x=3 /:3
x=1
d)-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 /:(-6)
x=-5
e)-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15 /:(-10)
x=1,5
f)4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10 /:(-2)
x=-5
32 4 32